2018
DOI: 10.1590/1980-57642018dn12-040002
|View full text |Cite
|
Sign up to set email alerts
|

Metamemory monitoring in Alzheimer’s disease A systematic review

Abstract: Metamemory is the awareness of one’s own knowledge and control of memory, and refers to the online ability to gather information about the current state of the memory system.Objective:Metamemory is one’s own knowledge and control of memory. A systematic review was performed to identify the types of tasks used for evaluating metamemory monitoring, the stimuli used in these tasks, their limitations and the outcomes in people with Alzheimer’s disease (PwAD).Methods:This systematic review followed PRISMA methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Normal older individuals seem to be reliable in their estimation of memory functioning, and there is some research suggesting good awareness in cognitively impaired subjects . In addition, the subjective memory report in HUNT was related to recent experience which promotes the reliability of the report according to a systematic review of meta‐memory . These findings and studies of individuals developing Alzheimer's disease lend support to an association between subjective cognitive complaints and objective memory abnormality Furthermore, the degree of self‐reported subjective impairment was associated with the degree of cognitive impairment in the present study as patients with mild dementia (MMSE ≥ 17) reported fewer concerns than those with more advanced dementia (MMSE ≤ 16).…”
Section: Discussionsupporting
confidence: 75%
“…Normal older individuals seem to be reliable in their estimation of memory functioning, and there is some research suggesting good awareness in cognitively impaired subjects . In addition, the subjective memory report in HUNT was related to recent experience which promotes the reliability of the report according to a systematic review of meta‐memory . These findings and studies of individuals developing Alzheimer's disease lend support to an association between subjective cognitive complaints and objective memory abnormality Furthermore, the degree of self‐reported subjective impairment was associated with the degree of cognitive impairment in the present study as patients with mild dementia (MMSE ≥ 17) reported fewer concerns than those with more advanced dementia (MMSE ≤ 16).…”
Section: Discussionsupporting
confidence: 75%
“…Anosognosia, the lack of self-awareness, is a common symptom of ADD [14][15][16][17][18]. As the disease progresses, persons with dementia have increased diffi culty refl ecting on their own actions objectively.…”
Section: Awareness Of Behavioral Psychological Symptoms Of Dementiamentioning
confidence: 99%
“…Consequently, it becomes difficult to predict others’ reactions and respond accordingly because of the deterioration of thinking abilities. Monitoring and managing one's own behaviors also becomes difficult, owing to the deterioration of self‐monitoring and self‐control abilities …”
Section: Introductionmentioning
confidence: 99%